2021
DOI: 10.3390/ijms22094808
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activity of New Brassinosteroid Analogs of Type 24-Nor-5β-Cholane and 23-Benzoate Function in the Side Chain

Abstract: Brassinosteroids are polyhydroxysteroids that are involved in different plants’ biological functions, such as growth, development and resistance to biotic and external stresses. Because of its low abundance in plants, much effort has been dedicated to the synthesis and characterization of brassinosteroids analogs. Herein, we report the synthesis of brassinosteroid 24-nor-5β-cholane type analogs with 23-benzoate function and 22,23-benzoate groups. The synthesis was accomplished with high reaction yields in a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Thus, BRs activity can be detected and quantified through a series of different plant responses, and, consequently, various bioassays have been proposed. It has been shown that different BRs activities are obtained by using different biological activity tests; this means that the results obtained by using different methods are not equivalent and cannot be compared [ 40 ]. This is a very important factor to be considered for a comparison of BRs activities and the proposal of structure–activity relationships of synthetic BRs analogs [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, BRs activity can be detected and quantified through a series of different plant responses, and, consequently, various bioassays have been proposed. It has been shown that different BRs activities are obtained by using different biological activity tests; this means that the results obtained by using different methods are not equivalent and cannot be compared [ 40 ]. This is a very important factor to be considered for a comparison of BRs activities and the proposal of structure–activity relationships of synthetic BRs analogs [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, compound 3 was found to be more active than brassinolide ( 1 ) ( Figure 1 ) at all tested concentrations [ 39 ]. On the other hand, compounds 5 and 6 were also evaluated in RLIT, and the 5 / 6 diastereoisomer mixture (ratio 1:0/0.44) is significantly more active than brassinolide at 1 × 10 −8 M concentration [ 40 ]. These results suggest that the incorporation of a benzoate group at the C-23 position of the side chain induces an increase in the biological activity of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, cytokinin-and auxin-like activities can be determined using a cucumber cotyledon bioassay (Fletcher et al 1982;Zhao et al 1992), the content of abscisic acids can be estimated using a wheat coleoptile straight growth bioassay (Zhao et al 1992), while the concentration of BRs can be assessed using bean second internode (Mandava 1988) and rice lamina inclination bioassays (RLIA) (Han et al 1997). The RLIA is the most commonly used biotest for BR detection due its specificity and sensitivity (Soto et al 2021). No bioassay has yet been used to determine the BR content of microalgae.…”
Section: Introductionmentioning
confidence: 99%